Insights into the recent advances in nano-bioremediation of pesticides from the contaminated soil - Singh, Yashpal; Saxena, Mumtesh Kumar (Frontiers in Microbiology, 2022)
In the present scenario, the uncontrolled and irrational use of pesticides is affecting the environment, agriculture and livelihood worldwide. The excessive application of pesticides for better production of crops and to maintain sufficient food production is leading to cause many serious environmental issues such as soil pollution, water pollution and also affecting the food chain. The efficient management of pesticide use and remediation of pesticide-contaminated soil is one of the most significant challenges to overcome. The efficiency of the current methods of biodegradation of pesticides using different microbes and enzymes depend on the various physical, chemical condition of the soil and has certain limitations. Hence a novel strategy is the need of the hour to safeguard the ecosystem from the serious environmental hazard. In recent years, the application of nano-materials has drawn attention in many areas due to their unique properties of small size and increased surface area. Nanotechnology is considered to be a promising and effective technology in various bioremediation processes and provides many significant benefits for improving the environmental technologies using nano-materials with efficient performance. The present article focuses on and discusses the role, application and importance of nano-bioremediation of pesticides and toxic pollutants to explore the potential of nanomaterials in the bioremediation of hazardous compounds from the environment.